The Effects of Four Different Thawing Methods on Quality Indicators of Amphioctopus neglectus - Zhang, Huixin; Liu, Shuji; Li, Shuigen; Chen, Xiaoe; Xu, Min; Su, Yongchang; Qiao, Kun; Chen, Xiaoting; Chen, Bei; Zhong, Hong; Lin, Hetong; Liu, Zhiyu (Foods, 2024)
Amphioctopus neglectus is a species of octopus that is favored by consumers due to its rich nutrient profile. To investigate the influence of different thawing methods on the quality of octopus meat, we employed four distinct thawing methods: air thawing (AT), hydrostatic thawing (HT), flowing water thawing (FWT), and microwave thawing (MT). We then explored the differences in texture, color, water retention, pH, total volatile basic nitrogen (TVB–N), total sulfhydryl content, Ca2+–ATPase activity, and myofibrillar protein, among other quality indicators in response to these methods, and used a low-field nuclear magnetic resonance analyzer to assess the water migration that occurred during the thawing process. The results revealed that AT had the longest thawing time, leading to oxidation-induced protein denaturation, myofibrillar protein damage, and a significant decrease in water retention. Additionally, when this method was utilized, the content of TVB–N was significantly higher than in the other three groups. HT, to a certain extent, isolated the oxygen in the meat and thus alleviated protein oxidation, allowing higher levels of Ca2+–ATPase activity, sulfhydryl content, and springiness to be maintained. However, HT had a longer duration: 2.95 times that of FWT, resulting in a 9.84% higher cooking loss and a 28.21% higher TVB–N content compared to FWT. MT had the shortest thawing time, yielding the lowest content of TVB–N. However, uneven heating and in some cases overcooking occurred, severely damaging the protein structure, with a concurrent increase in thawing loss, W value, hardness, and shear force. Meanwhile, FWT improved the L*, W* and b* values of octopus meat, enhancing its color and water retention. The myofibrillar protein (MP) concentration was also the highest after FWT, with clearer subunit bands in SDS-PAGE electrophoresis, indicating that less degradation occurred and allowing greater springiness, increased Ca2+–ATPase activity, and a higher sulfhydryl content to be maintained. This suggests that FWT has an inhibitory effect on oxidation, alleviating protein oxidation degradation and preserving the quality of the meat. In conclusion, FWT outperformed the other three thawing methods, effectively minimizing adverse changes during thawing and successfully maintaining the quality of octopus meat.